Solving a multistage partial inspection problem using genetic algorithms - Heredia-Langner, A.; Montgomery, D. C.; Carlyle, W. M. (International journal of production research, 2002)
Traditionally, the multistage inspection problem has been formulated as consisting of a decision schedule where some manufacturing stages receive full inspection and the rest none. Dynamic programming and heuristic methods (like local search) are the most commonly used solution techniques. A highly constrained multistage inspection problem is presented where all stages must receive partial rectifying inspection and it is solved using a real-valued genetic algorithm. This solution technique can handle multiple objectives and quality constraints effectively.